Pengaruh Nilai dan Kepuasan Terhadap Loyalitas Pelanggan Toyota Liek Motor Mojokerto - Silvana Praditya P (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The research was motivated by the intense competition in the business world, especially in the automotive world. Liek Toyota Motor Mojokerto continually strive to maintain customer because the customer is a major asset of the company. To retain these customers can be done by considering the value and customer satisfaction. This research included in this type of explanatory research in accordance with the purpose of this study was to determine how the variables influence the value and satisfaction to customer loyalty at Liek Toyota Motor Mojokerto and which variables between value and satisfaction over the dominant influence on customer loyalty. Customer population at Toyota Motor Liek Mojokerto from August-October 2012 amounted to 232 people and obtained a sample of 70 respondents using purposive sampling techniques or sampling techniques with particular consideration for example by taking samples taken policy is the customer who made a purchase at Toyota Motor Liek Mojokerto. Test used is the test of validity, reliability test, which includes the classic assumption test normality test, multicollinearity, heteroscedasticity test, autocorrelation test, whereas multiple regression analysis using the F test and the test T.Keywords: Influence, value, saticfaction, customers loyalty